Binding of dietary polyphenols to cellulose: Structural and nutritional aspects. (15th March 2015) - Phan, Anh Dao T.; Netzel, Gabriele; Wang, Dongjie; Flanagan, Bernadine M.; D'Arcy, Bruce R.; Gidley, Michael J.
Highlights: Diverse polyphenols bind to cellulose with comparable extents and rates. The chemical characteristics of polyphenols play a role in modulating binding. Native charge of polyphenols does not greatly affect binding to cellulose. The Langmuir isotherm model can be applied to quantify binding equilibria. Abstract: The interactions between polyphenols and plant fibres play an important role in controlling the release of phenolic compounds from food matrices for absorption in the gastrointestinal tract. This study probed the molecular interactions of diverse polyphenols with cellulose fibres by using a pure cellulose-producing bacterial model. Alkali treatment of bacterial cellulose was an effective method for obtaining a high purity cellulose model for study of polyphenol binding. Representatives of different polyphenol classes all bound to cellulose spontaneously, rapidly, and to comparable extents (up to 60% w/w of cellulose). Langmuir binding isotherms were applied to determine quantitative aspects of the adsorption at equilibrium. The study indicated that binding was similar on a molar basis for ferulic acid, gallic acid, catechin and cyanidin-3-glucoside (but lower for chlorogenic acid), with the native charge of polyphenols a secondary factor in the interactions between polyphenols and cellulose.